USING TEAMS GAMES TOURNAMENT (TGT) MODEL ASSOCIATED WITH SNAKES AND LADDER GAMES MEDIA TO IMPROVE STUDENTS' LEARNING ACTIVITIES AT GRADE V OF SDN 13 KAPALO KOTO, PADANG - Dea Sinta Maharani; Junaidi Indrawadi; Ulil Amri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the results of observations that students’ learning activities were still low. This was due to the Covid-19 pandemic that hit the world so that the learning process was carried out online. The online learning process did not stimulate students to carry out learning activities so that the students' learning activities were low. This study aimed to increase students’ learning activities by using Cooperative learning model of the Teams Games Tournament (TGT) type assisted by the snake and ladder game media. This research was classroom action research consisting of two cycles with 4 stages, namely planning, implementation, observation and reflection. The subjects of this study were 31 students of class VB. The data collection method used in this research was observation. The results showed that the average percentage of students’ learning activities classically increased. This was seen from the results of observations of students’ learning activities in cycle 1 which was 64.52% and in cycle 2 for 85.28%. Based on the results of this study, it was concluded that using TGT type cooperative model with snakes and ladders game media improved students’ learning activities.